Estudio de prefactibilidad para la instalación de una planta procesadora de hamburguesas de carne de res (Bos primigenius taurus) enriquecidas con harina de semilla de moringa oleifera - Gamarra Salcedo, Raul Sebastian (2023)
The objective of the present work is to determine the economic-financial pre-feasibility of a beef-based hamburger processing plant with an addition of moringa olifera. Thus, a survey was applied to 203 persons in metropolitan Lima, who meet the characteristics of the project's target consumer, obtaining a demand for 32 369 bags of 4 units of hamburgers during year 1 and projecting an annual growth of 4 %. In the macro and micro location study multiple factors were evaluated such as the availability of raw materials, proximity to the end customer, plant rental rates and proximity to the production and distribution centers of beef suitable for human consumption, also called slaughterhouses. It is concluded that the processing plant must be installed in Metropolitan Lima in the district of Lurín. The industrial plant is designed for an installed capacity of 45 823 commercial units per year, covering market demand throughout the project horizon. It has a semi-automatic production process made up of 12 workstations in sequence, in which there are 5 fully electric machines, and the rest of the activities are manual processes. Besides, the production process and logistics flow are aligned to quality standards determined by the NTPS defined for the project and using of the HACCP system. On the other hand, the industrial plant has around 500 m2, including the maneuvering yard. The project will be carried out with six persons for operational tasks and four persons for administrative tasks. Finally, the economic indicators recorded a NPV of S/ 313 513, an IRR of 34 %, a B/C of 1,53 and a recovery period of 2,93 years. In addition, the financial indicators will reflect a NPV of S/ 233 205, an IRR of 46 %, a B/C of 1,98 and an investment recovery period of 2,49 years.